A missense point mutation (Ser515Phe) in the adrenoleukodystrophy gene in a family with adrenomyeloneuropathy: a clinical, biochemical, and genetic study. Issue 2 (February 1995) - Vorgerd, M; Fuchs, S; Tegenthoff, M; Malin, J P
Abstract : A 36 year old male patient with adrenomyeloneuropathy (AMN) developed progressive spastic paraparesis and sensory ataxia from the age of 18. Biochemical studies showed increased plasma concentrations of saturated very long chain fatty acids (VLCFAs), subclinical evidence of adrenal insufficiency, and primary hypogonadism. Three female family members had increased plasma concentrations of VLCFAs, suggesting carrier status of adrenoleukodystrophy (ALD). Molecular genetic analysis detected a missense point mutation (C1930T) in exon 6 within the ALD gene, which predicts substitution of an amino acid (Ser515Phe) that is conserved between the deduced amino acid sequence of the peroxisomal membrane protein PMP70 and ALD protein. Detection of this point mutation allows diagnosis of ALD or AMN, identification of heterozygotes, and prenatal diagnosis of ALD.